Resolution of the National Multidisciplinary Research Council of Experts on the place of anti-interleukin-6 receptor monoclonal antibodies (Sarilumab) in the treatment of patients with rheumatoid arthritis and comorbidity - article Editorial (Научно-практическая ревматология)
.